Design of a biodigester to reduce organic waste and generate biogas in a Basic School. - Morales Cárdenas, Verónica Andrea (LACCEI, 2025)
The design of a biodigester for Basic School D-271 Los Cerrillos, located in the southwest sector of Santiago, the capital of Chile, aims to manage organic waste and generate biogas efficiently. To determine the appropriate dimensions and volume, the kitchen waste was first classified and quantified to define the substrate composition. This composition was then adjusted to achieve an optimal carbon/nitrogen ratio. The moisture content of the adjusted substrate was calculated, and the precise amount of water needed for a balanced feed was determined. The bioreactor was sized based on the estimated feeding volume. The theoretical volume of biogas per cycle was also calculated, and the dimensions of the gasometer were established. The selection of the biodigester type considered the mode of operation, substrate moisture, and hydraulic retention time. The results of this project meet the school’s needs and represent a significant step towards sustainability and intelligent waste management in the educational environment. Keywords: Biodigester, Organic waste, Biogas, Sustainability, Waste management